If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5n + -4 = -19 Reorder the terms: -4 + 5n = -19 Solving -4 + 5n = -19 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 5n = -19 + 4 Combine like terms: -4 + 4 = 0 0 + 5n = -19 + 4 5n = -19 + 4 Combine like terms: -19 + 4 = -15 5n = -15 Divide each side by '5'. n = -3 Simplifying n = -3
| -8(3x+7)=28+4x | | 5+7(7-8a)=390 | | 15=(2t-1) | | f(x)=(x-5)(x+6)(x+2) | | (x^2-6x+18)(x+1)= | | 0.4x+4.9=3.9 | | -2(1-8k)=126 | | 2a-7a=2a | | (5x+6)(4y-5)= | | 5(6x-4)=220 | | -5x+1=12x+1 | | R-4=-9+r | | -5x+1=112x+1 | | -2(v-7)=22-6v | | 5a=x | | 2x+3(2-7)=9 | | y(y-1)=-6 | | -4n-5(n-4)=92 | | 1xf=7 | | 2(5)-(14-5)=x | | 2N-9N=6N+52 | | 168=4(-5p+7) | | 2(5)-(14-5)=1 | | 2p+3p=10 | | [x-(3+3i)][x-(3-3i)]= | | -15-3k=-1+4k | | 3x^2+2x-49=0 | | 4x-2=22-8r | | 6=-2n+8n | | -12=-(5x-8)+8(2x-8) | | 10=1+3v-6v | | 2b+12=3b-31 |